Effect of branching angle on a leaf-like flow channel - Goh, Rui Ren (2017)
Implementation of microscale heat transfer in macro geometry is uncommon due to cost and manufacturability constraints. Conventional readily-available machining methods were proposed to overcome the challenges. An annular microchannel of 300 μm is created using an insert, 19.4 mm in diameter which is, placed concentrically into a circular channel of 20 mm diameter. Both insert and hollow copper pipe were fabricated using readily-available turning and milling process. In steady-state single-phase liquid heat transfer, undesirable pressure drop increment tags along with enhanced heat transfer. This study aims to reduce the hydrodynamic resistance of fluid flow. As leaf venation is a form of ramifying structure similar to other natural-existing flow system like the lung and river delta, it is envisioned to generate minimum flow resistance. Previous studies have shown bifurcation angle is an important variable to reducing pressure drop. As such, leaf surface profiles with varying bifurcation angles of 55, 65, 75 and 85 degree were designed to study its effect in microchannel fluid flow. The heat transfer and hydrodynamic performance for the inserts were evaluated after experimental runs. Results show that Leaf_55 insert achieved a convective heat transfer coefficient, h of 45.82 kW/m2·K, 5% higher than Leaf_85 insert at Reynolds number of 4616. Even at Reynolds number of 1393, the former achieved that of 19.82 kW/m2·K, 19.8% more than Leaf_65 insert. In terms of heat transfer performance, all the leaf designs are equally good as their h fall under the uncertainty range. By keeping the flow in the minimum gap consistent between the surface profile and inner pipe wall, the heat transfer enhancement due to local effects becomes insignificant. However, Leaf_55 insert also induces the greatest pressure drop among the others. The comparison to Leaf_85 is that Leaf_55 incurs 33% and 23% more pressure drop, at the lowest and highest Re respectively. The highlight of the results indicates that Leaf_85 microchannel achieved a maximum performance index of 1.33 at Re of 2362, capable of removing 33% extra heat with equivalent pumping power consumed as compared to plain microchannel. Bifurcation angle has also been analysed to be critical in lowering pressure drop.